Pengaruh Ketimpangan Gender dan Tingkat Pendidikan terhadap Partisipasi Angkatan Kerja di Pulau Sumatera Tahun 2019-2023 - Ginting, Hilkia; Hartato Rianto (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of gender inequality and educational attainment on labor force participation in Sumatra from 2019 to 2023. Gender disparities and limited access to quality education are key factors affecting low workforce participation, particularly among women and individuals with lower education levels. The research employs a quantitative approach using secondary data from the Central Bureau of Statistics (BPS).